Health and wellbeing during transition to adulthood for young people with intellectual disabilities: A qualitative study. (November 2017) - Young-Southward, Genevieve; Cooper, Sally-Ann; Philo, Christopher
Abstract: Background: Transition to adulthood may have negative consequences for health and wellbeing in individuals with intellectual disabilities (ID), but this aspect of transition has received little investigation. This qualitative study aimed to explore the transition experiences of individuals with ID from their own perspectives, and from that of their parents, in order to identify health or wellbeing implications of transition. Method: Semi-structured interviews were conducted with 17 young people with mild, moderate and severe ID aged 16–27 years and with 23 parents of young people with mild, moderate, severe and profound ID aged 16–26 years. Interviews were analysed using thematic analysis, deploying both emic and etic coding categories. Results: This study provides direct insights into the issues on health and wellbeing that young people with ID and their parents find important during transition. The primary health implication of transition centred on mental health and wellbeing; young people experienced heightened anxiety during transition, and themes identified as contributing to anxiety included: a lack of meaningful activity following school exit; inadequate support during transition; and difficulties associated with 'growing up'. Problem behaviours and obesity were also implicated. Conclusion: The transition from school needs to be better supported in order to ease anxiety for young people during this difficult period.